Chimpanzees Predict the Hedonic Outcome of Novel Taste Combinations: The Evolutionary Origins of Affective Forecasting - Sauciuc, Gabriela-Alina; Persson, Tomas (Frontiers in Psychology, 2020)
Affective forecasting - predicting the emotional outcome of never-before experienced situations - is pervasive in our lives. When facing novel situations, we can quickly integrate bits and pieces of prior experiences to envisage possible scenarios and their outcomes, and what these might feel like. Such affective glimpses of the future often steer the decisions we make. By enabling principled decision-making in novel situations, affective forecasting confers the important adaptive advantage of eluding the potentially costly consequences of tackling such situations by trial-and-error. Affective forecasting has been hypothesized as uniquely human, yet, in a recent study we found suggestive evidence of this ability in an orangutan. To test nonverbal subjects, we capitalized on culinary examples of affective forecasting and devised a behavioral test that required the subjects to make predictions about novel juice mixes produced from familiar ingredients. In the present study, we administered the same task to two chimpanzees and found that their performance was comparable to that of the previously tested orangutan and 10 humans, who served as a comparison group. To improve the comparability of human and animal performance, in the present study we also introduced a new approach to assessing if the subjects’ performance was indicative of affective forecasting, which relies exclusively on behavioral data. The results of the study open for the possibility that affective forecasting has evolved in the common ancestor of the great apes, providing Hominids with the adaptive advantage of e.g. quickly evaluating heterogeneous food patches using hedonic prediction.